Supporting medicines management for older people at care transitions - a theory-based analysis of a systematic review of 24 interventions - Justine Tomlinson; Iuri Marques; Jonathan Silcock; Beth Fylan; Judith Dyson (BMC, 2021)
Abstract Background Older patients are at severe risk of harm from medicines following a hospital to home transition. Interventions aiming to support successful care transitions by improving medicines management have been implemented. This study aimed to explore which behavioural constructs have previously been targeted by interventions, which individual behaviour change techniques have been included, and which are yet to be trialled. Method This study mapped the behaviour change techniques used in 24 randomised controlled trials to the Behaviour Change Technique Taxonomy. Once elicited, techniques were further mapped to the Theoretical Domains Framework to explore which determinants of behaviour change had been targeted, and what gaps, if any existed. Results Common behaviour change techniques used were: goals and planning; feedback and monitoring; social support; instruction on behaviour performance; and prompts/cues. These may be valuable when combined in a complex intervention. Interventions mostly mapped to between eight and 10 domains of the Theoretical Domains Framework. Environmental context and resources was an underrepresented domain, which should be considered within future interventions. Conclusion This study has identified behaviour change techniques that could be valuable when combined within a complex intervention aiming to support post-discharge medicines management for older people. Whilst many interventions mapped to eight or more determinants of behaviour change, as identified within the Theoretical Domains Framework, careful assessment of the barriers to behaviour change should be conducted prior to intervention design to ensure all appropriate domains are targeted.